Resiliensi Bisnis Berbasis Digital: Evaluasi Keberlanjutan Praktik Akuntansi Modern pada UMKM di Kota Tangerang - Florencia Irena Lawita; Dading Damas Ario Wicaksono; Teguh Yanto; Natasha Richelle Valencia Ibrahim (Owner : Riset dan Jurnal Akuntansi, 2026)
Amidst global economic uncertainty, accounting digitalization has become a crucial tool for Micro, Small, and Medium Enterprises (MSMEs) to maintain their existence. However, the transition from traditional accounting to digital systems often faces obstacles in terms of consistency and sustainability of implementation. Tangerang City, as a center of heterogeneous economic activity, provides a unique landscape to evaluate the extent to which modern accounting practices are not only technically adopted but also internalized as a business resilience strategy. This qualitative research aims to explore in-depth the sustainability of modern digital-based accounting practices as a resilience strategy for MSMEs in Tangerang City. The main focus of the research is to understand the dynamics of technology adoption, psychosocial barriers, and long-term use of digital accounting systems. Using a descriptive case study approach, data were collected through in-depth interviews with MSME owners who have integrated accounting applications into their operations, as well as field observations. The research results reveal that business resilience is determined not only by technological sophistication, but by changes in mindset and the integration of financial data into daily decision-making. The sustainability evaluation reveals challenges in the form of digital fatigue and dependence on third-party platform ecosystems. This study concludes that the sustainability of modern accounting practices in MSMEs requires the support of practical communities and ongoing technical assistance from local governments to mitigate the risk of technological discontinuity.